Walking the creek: reconnecting place through light projection. (9th May 2019) - Edensor, Tim; Andrews, Julie
Abstract: In this paper, we explore how a light projection sought to convey a range of qualities: conviviality, a sense of place, playfulness, defamiliarisation, and the affective and sensory capacities that were experienced through walking in the distinctive, liminal realm of Bendigo Creek in Victoria, Australia. The projection aspired to solicit a sensory and affective empathy that chimed with the experiences of an earlier event in which dozens of pedestrians were filmed walking in the creek. The projection contributed to a local campaign to reappraise the much‐maligned creek as a local public amenity. We discuss the productive potential of solitary and collective walking and, subsequently, the attributes of the projection in its static and mobile manifestation. In so doing, we suggest that publicly engaged, inclusive, creative practice can offer potent place‐making possibilities.